Planning in a changing context: French policies of regionalisation since 1945 - BENKO, Georges; STROHMAYER, Ulf (European Spatial Research and Policy, 1998)
This report synthesizes the main strands of regional planning in France since the end of the Second World War. lt highlights the principally political reasons behind the creation an subsequent recreation of instruments used for and in the process of ’planning spaces’. The region long since held to be a staple of geographic enquiry, here emerges as a highly contested an politically charged concept that is subject to frequent abrupt changes in govemment policies. Th report concludes with a brief outlook upon changes brought about by the Frcnch legislativ elections earlier in 1997.